STRATEGI METAKOGNITIF DALAM PEMBELAJARAN BAHASA INDONESIA MENGGUNAKAN VIDEO DI KELAS IV SDN 70 BANDA ACEH - Istiqamah; Regina Rahmi; Raziska Ibrahimi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesian language learning in elementary schools plays a crucial role in developing critical thinking skills and student learning awareness. However, learning still tends to be teacher-centered and does not fully train students to be aware of their own thinking processes. One effort that can be made to address this problem is the implementation of metacognitive strategies combined with the use of video learning media. This study aims to describe the application of metacognitive strategies in Indonesian language learning using video media and its impact on the critical thinking skills of fourth grade students at SD Negeri 70 Banda Aceh. This study used a descriptive qualitative approach with a case study design. Data collection techniques were conducted through observation, interviews, and documentation. The research subjects consisted of one teacher and several fourth grade students. The results of the study indicate that the application of metacognitive strategies, including planning, monitoring, and evaluation, can improve students' engagement, understanding, and awareness of their learning process. The use of instructional video media can capture students' attention, increase their motivation to learn, and help them understand the material on differentiating facts from opinions more concretely. Students demonstrated positive responses, expressed their opinions more confidently, and gained greater confidence in participating in the learning process. Therefore, the application of metacognitive strategies supported by instructional video media is considered effective in improving the quality of Indonesian language learning and critical thinking skills of fourth-grade students at SD Negeri 70 Banda Aceh